Effect of Menopausal Hormone Therapy on the Vaginal Microbiota and Genitourinary Syndrome of Menopause in Chinese Menopausal Women - Geng, Lulu; Huang, Wenjun; Jiang, Susu; Zheng, Yanwei; Zhou, Yibei; Zhou, Yang; Hu, Jiangshan; Li, Ping; Tao, Minfang (Frontiers in Microbiology, 2020)
Genitourinary syndrome of menopause (GSM) is a chronic and progressive condition with a series of vulvovaginal, sexual as well as lower urinary tract discomforts, mainly due to hypoestrogenism. Menopause hormone therapy (MHT) has been generally considered as the most effective treatment for it. Besides, vaginal microbiota is of particular significance to gynecological and reproductive illnesses and potentially have some intimate connections with GSM. In consequence, we sought to evaluate how MHT impact the composition and structure of vaginal microbiota while alleviating GSM in Chinese menopausal women aged 45 to 65, which has not been investigated previously. 16S rRNA gene sequencing was performed to analyze microbial diversity and composition through using vaginal swabs obtained from 100 menopausal women, classified as MHT women who has been taking tibolone regularly (n=50) and non-treated women who never received any treatment (n=50), and Vaginal Health Index Score (VHIS) and GSM symptoms inquiry were also performed. We found that vaginal microbial diversity decreased and abundance of Lactobacillus increased to the dominant proportion significantly in MHT group, in considerable contrast to vaginal microbiota of non-treated group that significantly comprised several anaerobic bacteria, namely, Gardnerella, Prevotella, Escherichia-Shigella, Streptococcus, Atopobium, Aerococcus, Anaerotruncus and Anaerococcus. In this study, women without any MHT had significantly severer GSM symptoms than those receiving tibolone, especially for vulvovaginal dryness and burning as well as decreased libido (p<0.01). However, there was no significant difference in the severity of urological symptoms between both groups (p>0.05). Furthermore, Lactobacillus was demonstrated to be associated with VHIS positively (r=0.626, p<0.001) and with GSM negatively (r=-0.347, p<0.001). We also identified Chlamydia (r=0.277, p<0.01) and Streptococcus (r=0.270, p<0.01) had prominent association with more serious GSM symptoms. Our study provided an elucidation that MHT could alleviate GSM notably and reshape the composition of the vaginal microbiota conspicuously, of extreme importance to clinical practice for management of GSM.